Reduced graphene oxide coated modified SnO2 forms excellent potassium storage properties. Issue 10 (15th May 2023) - Wu, Shanshan; Feng, Yefeng; Jiang, Wenqin; Wu, Kaidan; Guo, Zhiling; Xiong, Deping; Chen, Li; Feng, Zuyong; Wen, Kunhua; He, Miao
Abstract: In this work, SnO2 and Sn nanoparticles adhered to the surface of rGO (SnO2 /Sn/rGO) applied as potassium ion batteries (KIBs) anode materials were synthesized via thermal reduction. Preparing SnO2 material into a nanostructure for modification can reduce ion diffusion distance to improve the number of active sites appropriate for K + adsorption, and efficiently reduce the volume change which is conducive to enhancing the potassium storage capacity. Besides, layered rGO inhibits SnO2 /Sn aggregation, while increased surface area also reduces diffusion channel and electrolyte contact. However, larger specific surface area result in a lower initial Coulomb efficiency (ICE). The approach adopted here is to force the solid electrolyte interface (SEI) to fully emerge during the first charge-discharge cycle by using electrolytes containing 1 M KFSI in EC and DEC (1:1, v/v). According to density functional theory (DFT) analysis, the doping of rGO and SnO2 effectively enhanced the adsorption of potassium atoms and reduced the diffusion barrier of K + . Therefore, SnO2 /Sn/rGO nanocomposites have a high specific capacity (325.8 mAhg −1 after 350 cycles at 0.1 Ag -1 ), an excellent ICE (66.57%), and a long cycle life (203.6 mAhg −1 after 1000 cycles at 0.5 Ag -1 ).